Farmers’ Perception about Impact of Sale of Buffaloes on Dairy Development Index and Socio-economic Conditions in Haryana (Indian Journal of Extension Education, 2017)
Sale of buffaloes provides much needed cash to the farmers. However, it is also believed that due to it, valuable germplasm is being lost. Therefore, to examine the issue the study was conducted in Murrah Breeding tract of Haryana i.e. Hisar, Bhiwani, Rohtak and Jind districts. Out of these districts one village having maximum number of buffaloes sold as identified by the traders and one village having comparatively less sale of buffaloes were selected. Thus, two villages were selected from each district and the study was conducted in 8 villages of 4 districts of Haryana. On the basis of number of buffaloes sold i.e. 1-2, 3-5 and more than 5 buffaloes during the last 5 years proportionate random sampling was done to have a sample of 30 farmers from each village. Thus, 240 farmers constituted the study sample. Perceived impact of sale of buffaloes on the socio-economic conditions and dairy development index of farmers was studied in two categories of villages. Z-value of 14.81 and 14.77 indicated that due to sale of buffaloes farmers perceived that the socio-economic conditions improved as they had more income, better material possession, better economic motivation etc. It was also observed that there was better adoption of improved buffalo husbandry practices like AI, balanced feeding, health and management, calf management etc. Dairy Development Index (DDI) of individual farmers was calculated for all the eight villages by a formula suggested by Dixit and Laharia (1999). Mean DDI of villages from where maximum sale of buffaloes took place was 2.74 while it was 2.22 from the set of villages where it was comparatively less. Z-value of 4.85 indicated that Dairy Development Index of those villages from where maximum buffaloes were sold was better. Thus, it can be inferred that farmers feel sale of buffaloes improved socio-economic status of farmers, their adoption of improved buffalo husbandry and dairy development index of those villages from where maximum sale of buffaloes took place.